FACTORS AFFECTING E-LEARNING USER ACCEPTANCE LEVEL USING TECHNOLOGY READINESS ACCEPTANCE MODEL (TRAM) (CASE STUDY: JAMBI UNIVERSITY) - yolanda (JUSS (Jurnal Sains dan Sistem Informasi), 2022)
i-LMS UNJA (E-learning Jambi University) is a Jambi University online learning medium that facilitates the implementation of free lectures or information and communication technology assistance. This study aims to determine the factors that affect the level of acceptance of e-learning users using the Technology Readiness Acceptance Model (TRAM). This research was conducted by using purposive sampling method, namely the sampling technique by determining certain criteria in sampling. The number of respondents who were determined as samples in this study were 105 respondents who have used E-learning Jambi University based on Hair theory. The analysis technique used to interpret and analyze the data in this study is the Structural Equation Model (SEM) technique using Partial Least Square (PLS) software to determine the influence between variables in the research model. The final result of this research is that it is known that the hypothesis of the variables that affect the level of acceptance of e-learning users is 7 accepted with a T-statistic value> 1.96 and three rejected with a T-statistic value <1.96.